Do phase-dependent life history traits in cyclic voles persist in a common environment? - Sundell, Janne (Oecologia, 2019)
Phenotype and life history traits of an individual are a product of environmental conditions and the genome. Environment can be current or past, which complicates the distinction between environmental and heritable effects on the phenotype in wild animals. We studied genome–environment interactions on phenotype and life history traits by transplanting bank voles (Myodes glareolus) from northern and southern populations, originating from low or high population cycle phases, to common garden conditions in large outdoor enclosures. The first experiment focused on the persistence of body traits in autumn-captured overwintering populations. The second experiment focused on population growth and body traits in spring-captured founder voles and F1 generation. This experiment lasted the breeding season and subsequent winter. We verified phase-dependent differences in body size at capture. In the common environment, adult voles kept their original body size differences both over winter and during the breeding season. In addition, the first generation born in the common environment kept the size distribution of their parent population. The increase phase population maintained a more rapid growth potential, while populations from the decline phase of the cycle grew slower. After winter, the F1 generation of the increasing northern population matured later than the F1 of the southern declining ones. Our results suggest a strong role of heredity or early life conditions, greater than that of current juvenile and adult environmental conditions. Environmental conditions experienced by the parents in their early life can have inter-generational effects that manifest in offspring performance. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00442-019-04410-3) contains supplementary material, which is available to authorized users.